CONVERGENCE AND DIVERGENCE BETWEEN THE EUROPEAN DIRECTIVES AND EUROPEAN COUNTRIES` FINANCIAL AUDIT LEGISLATION: EVIDENCE FROM ROMANIA AND REPUBLIC OF MOLDOVA - Dănescu, Tatiana; Popa, Maria Alexandra; Vasileva, Mariana (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 19 (2017): Annales Universitatis Apulensis Series Oeconomica, 2017)
Financial audit, by its object, is a mean of helping to stabilize the economy at national and international level, and a special concern is given to professional bodies, national and European authorities in developing regulations to improve, facilitate and, in at the same time, to standardize financial audit procedures. Each European country adopts laws, codes, ordinances, and practices that aim to comply with European standards. Drawing from this consideration, we conducted research on the basis of analyzing and comparing the financial audit legislation of two countries in the European geographical area, one member of the European Union (Romania) and one outside the EU area (Republic of Moldova), but with aspirations for integration in the European Union. The objective of this research is to identify and to analyze the convergences and divergences between the norms found in the two states in accordance with European directives.